2023
DOI: 10.1128/spectrum.02764-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Metabolite Profiling Reveal a Novel Streptomyces Strain, QHH-9511, from the Qinghai-Tibet Plateau

Abstract: Undescribed microorganisms from special habitats are being screened for anti-superbug drug molecules. In a project to screen actinomycetes for anti-MRSA activity, we isolated a Streptomyces strain from Qinghai Lake lichens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Actinomycetes have been one of the main sources of bioactive compounds used in medicine. With the fast development of sequencing and genomics, it has been observed that strains known for the production of one or a few molecules have the potential to produce many more unknown metabolites [10,11,19,20]. The Streptomyces species are a source of important antitumor compounds such as actinomycin, mitomycin, anthracycline, or bleomycin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actinomycetes have been one of the main sources of bioactive compounds used in medicine. With the fast development of sequencing and genomics, it has been observed that strains known for the production of one or a few molecules have the potential to produce many more unknown metabolites [10,11,19,20]. The Streptomyces species are a source of important antitumor compounds such as actinomycin, mitomycin, anthracycline, or bleomycin.…”
mentioning
confidence: 99%
“…Unfortunately, in recent decades, the rate of rediscovery of already-described molecules has frustrated many research efforts [21]. In order to find novel molecular structures, several different strategies are being followed, from manipulating the genome to forcing the expression of cryptic clusters (genome mining) [22] or looking for new strains in barely explored environments such as the Earth's poles, insect teguments, high altitudes, caves or marine sources [20,[23][24][25][26][27]. Several different cytotoxic compounds have been recently isolated from Streptomyces [28][29][30][31] In this work, we isolated microorganisms from marine sediments in Indonesia.…”
mentioning
confidence: 99%